Research on the Quality Properties of Wheat Noodles by Adding Debranched Wheat Starch - LIU Xian-zhi; ZHAN Lin-jie; LI Hong-yan; LI Cai-fu; LI Man; XU Tong-cheng; JI Na; XU Long-zhao (Liang you shipin ke-ji)
High-gluten wheat flour, debranched wheat starch (debranched supernatant and debranched precipitate), and gluten were used as raw materials, the influence of debranched wheat starch on the digestion characteristics, cooking properties, and thermal properties of rolled wheat noodles was studied. The results showed that adding debranched wheat starch could reduce the hardness and chewiness of wheat noodles. Relative crystallinity of noodles increased from 9.37% (control) to 18.25% (50% debranched supernatant). Compared with the control group, when 50% debranched precipitate was added, the noodles' gelatinization onset temperature (To), peak temperature (Tp), final temperature (Tc), and gelatinization enthalpy (ΔH) all increased, indicating improved thermal stability, and the resistant starch (RS) content increased from 11.37% to 22.19%, while the estimated glycemic index (eGI) decreased from 87.71 to 78.57, demonstrating good in vitro digestion results. The above study proved that the addition of debranched wheat starch could reduce the digestion rate of rolled noodles in vitro, and provided ideas and methods for the development of staple food products for patients with chronic blood sugar diseases.